Bisphosphonate Related Osteonecrosis of the Jaw: A Study of 18 Cases Associated with Fungal Infection - V. Aftimos; T. Zeinoun; R. Bou Tayeh; G. Aftimos (Hindawi Limited, 2014)
Osteonecrosis of the jaw (ONJ) is a serious complication associated with oral and intravenous bisphosphonate therapy. Its pathogenesis is not well understood and its management is difficult. Microbiological investigations have detected a variety of oral pathogens such as Actinomyces, Enterococcus, Candida albicans, Aspergillus, Haemophilus influenzae, alpha-hemolytic streptococci, Lactobacillus, Enterobacter, and Klebsiella pneumoniae. To better treat it, it is important to understand its causes and complications. Materials and Methods. Our present study addresses a microscopic observation of curetted jaw necrotic lesions related to bisphosphonates. Results. A mycotic infestation has been found in all of the 18 cases studied. Discussion. An identification of the fungal agent and its incrimination in the pathogenesis of bisphosphonates related osteonecrosis of the jaw could change radically the management of this condition.